α-Conotoxins and α-Cobratoxin Promote, while Lipoxygenase and Cyclooxygenase Inhibitors Suppress the Proliferation of Glioma C6 Cells - Tatiana I. Terpinskaya; Alexey V. Osipov; Elena V. Kryukova; Denis S. Kudryavtsev; Nina V. Kopylova; Tatsiana L. Yanchanka; Alena F. Palukoshka; Elena A. Gondarenko; Maxim N. Zhmak; Victor I. Tsetlin; Yuri N. Utkin (Marine Drugs, 2021)
Among the brain tumors, glioma is the most common. In general, different biochemical mechanisms, involving nicotinic acetylcholine receptors (nAChRs) and the arachidonic acid cascade are involved in oncogenesis. Although the engagement of the latter in survival and proliferation of rat C6 glioma has been shown, there are practically no data about the presence and the role of nAChRs in C6 cells. In this work we studied the effects of nAChR antagonists, marine snail α-conotoxins and snake α-cobratoxin, on the survival and proliferation of C6 glioma cells. The effects of the lipoxygenase and cyclooxygenase inhibitors either alone or together with α-conotoxins and α-cobratoxin were studied in parallel. It was found that α-conotoxins and α-cobratoxin promoted the proliferation of C6 glioma cells, while nicotine had practically no effect at concentrations below 1 µL/mL. Nordihydroguaiaretic acid, a nonspecific lipoxygenase inhibitor, and baicalein, a 12-lipoxygenase inhibitor, exerted antiproliferative and cytotoxic effects on C6 cells. nAChR inhibitors weaken this effect after 24 h cultivation but produced no effects at longer times. Quantitative real-time polymerase chain reaction showed that mRNA for α4, α7, β2 and β4 subunits of nAChR were expressed in C6 glioma cells. This is the first indication for involvement of nAChRs in mechanisms of glioma cell proliferation.